Vietnam : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria-Staff Report; Staff Statement; News Brief on the Executive Board Discussion; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2002)
This paper evaluates Vietnam's Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criteria. Under the first-year PRGF, Vietnam's economic performance was relatively strong, despite weak external demand. The goals under the second-year PRGF- supported program remain to boost investment and competitiveness as the bases for returning Vietnam's rates of growth and poverty reduction closer to potential. The key priorities are disciplined macroeconomic management and a firmer implementation of the structural agenda.